INFLUENCE OF DEPRESSION AND SELF-ESTEEM ON SUICIDAL IDEATION AMONG UNIVERSITY STUDENTS - Ajayi, Olubukola (Advances in Social Sciences Research Journal, 2020)
The research examined the influence of self- esteem and depression on suicidal ideation among university students. The research was carried out among university students to measure the influence of self- esteem and depression on suicidal ideation. Two hundred and fifty one participants [251] were sampled from a university for the purpose of this research. The instrument used for this research was questionnaire. The statistical methods used were t-test and one way ANOVA. Four hypotheses were tested and the result revealed: Students with high self-esteem [M =12.7877] significantly reported lower suicidal ideation than those with low self- esteem [M =18.5905], df [249] = -6.043, p <.01.The result implies that self-esteem influenced suicidal ideation among students. The results also shows that students with low depression [M = 12.8188] significantly reported lower suicidal ideation than those with high depression [M = 19.5222], df [248] = 6.903, p<.01. The result implies that depression influenced suicidal ideation among students. Likewise the result shows that female students [M =16.1301] were not significantly different from male students [M = 14.3359], df [249] =1.780, p>.05. The result implies that there is no gender difference in suicidal ideation among students. However students in 100 level of study [M =15.3469] were not significantly different in suicidal ideation compared to those in 200[M =14.7375], 300[M =14.5000], 400[M = 15.8036] and 500[M = 19.1000] levels of study. The result means that the level of study has no significant influence on suicidal ideation among students F[4,246] =0.846; p>.05.